Cross-National analysis of students' socio-economic status on the educational achievement - Sova, Jan; Sáenz de Viteri Vázquez, Andrea; Cingl, Lubomír, 1984-; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2022)
This thesis examines the effect of students' socio-economic status (SES) on educational outcomes, focusing on student achievement in math, science, and reading. Data are obtained from the population of 15-year-olds in 40 European countries from The Programme for International Student Assessment (PISA). A set of items on household possessions is used to measure the SES dimensions, which are used to construct a custom Household Possessions Index. Variables capturing the occupational status of the father and mother are also used, as well as variables capturing the education level of the father and mother. This thesis confirms that the constructed Household Possessions Index can be used as an indicator of SES. The first hypothesis that students with higher SES achieve better educational outcomes is confirmed based on student performance in math, science, and reading. The second hypothesis, that differences between countries in the strength of SES effects diminish over time, cannot be confirmed because of the mixed results across countries.
Vedoucí práce: Andrea Sáenz de Viteri Vázquez
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2022
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2022
Způsob přístupu: Internet
Keywords: ekonomie [obor dipl. práce]; diplomové práce; master's theses